Associations Between Non-Ergonomic Working Posture,Work-Related Stress, Smoking Habits, and Physical Activitywith Low Back Pain among Police Personnel in theSpecial Region of Yogyakarta - Mahardhika, Viola Widyanita; Sumardiyono, Sumardiyono; Murti, Bhisma; Novika, Revi Gama Hatta; Demartoto, Argyo (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Low back pain is one of the most common musculoskeletal complaints among police personnel. Several factors, including working posture, work-related stress, smoking habits, and physical activity, are presumed to be associated with the occurrence of low back pain. This study aimed to analyze factors associated with low back pain among police personnel. Subjects and Method: This analytic observational study with a cross-sectional design involved 226 male and female police personnel aged 20–40 years in the Special Region of Yogyakarta, selected using total sampling. The dependent variable was the occurrence of low back pain, while the independent variables included working posture, work-related stress, smoking habits, physical activity, age, and years of service. Data were collected using the Rapid Upper Limb Assessment (RULA) to assess working posture, the Police Stress Questionnaire–Operational (PSQ-Op) to measure work-related stress, and the Numeric Rating Scale (NRS) to assess low back pain intensity. Data were analyzed using the Chi-square test and path analysis. Results: Path analysis showed significant direct effects of non-ergonomic working posture (b = 0.19; 95% CI = 0.09 to 0.29; p < 0.001), work-related stress (b = 0.35; 95% CI = 0.23 to 0.46; p < 0.001), smoking habits (b = 0.17; 95% CI = 0.05 to 0.29; p = 0.007), physical activity (b = −0.16; 95% CI = −0.27 to −0.05; p = 0.006), and age (b = 0.11; 95% CI = 0.01 to 0.22; p = 0.034) on the occurrence of low back pain. Years of service had an indirect effect on low back pain through age (b = 0.99; 95% CI= 0.98 to 0.99; p < 0.001). Conclusion: Non-ergonomic working posture, work-related stress, smoking habits, physical activity, and age have direct effects on the occurrence of low back pain.